2019
DOI: 10.1186/s12913-019-4445-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a shared decision-making communication skills training for physicians treating patients with asthma: a mixed methods study using simulated patients

Abstract: Background Shared decision-making (SDM) is a key principle in asthma management, but continues to be poorly implemented in routine care. This study aimed to evaluate the impact of a SDM communication skills training for physicians treating patients with asthma on the SDM behaviors of physicians, and to analyze physician views on the training. Methods A mixed methods study with a partially mixed sequential equal status design was conducted to evaluate a 12 h SDM communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…However, evaluations covering the entire spectrum are rare. Assessing the program's impact on patient involvement in decisionmaking will be of particular importance in the broader context of the literature on SDM trainings [41] and TTT in general [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evaluations covering the entire spectrum are rare. Assessing the program's impact on patient involvement in decisionmaking will be of particular importance in the broader context of the literature on SDM trainings [41] and TTT in general [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating trainers' (ambassadors) learning outcomes and behaviours (rather than the trainee/patient variables) is a unique [40] although reasonable strategy, as suggested by a recent review [42] and the Kirkpatrick Model [27]. As part of the development process [24], this approach may lead to a better understanding about the best way to support trainers in training others, and a better understanding of the development of trainers' learning abilities and behaviour over time [41]. Our recruitment strategy resulted in a mix of participants who had been sent by their hospital trusts and participants who came of their own volition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Driever et al [ 29 ] reported that 31.0% made a decision using a paternalistic approach because they perceived that it was difficult for patients to make a decision, indicating that physicians and other healthcare professionals may create a barrier to SDM. To overcome such barrier, it is necessary to provide SDM communication skill training [ 30 ] and develop patient decision aids for Japanese patients, which are assistive tools that promote SDM.…”
Section: Discussionmentioning
confidence: 99%
“…61 Shared decisionmaking communication skills training courses for health-care providers have been developed, although their effectiveness is still underresearched and their implementation still insufficient. 60,62,63 Shared decision-making tools have also been developed for dsd conditions such as CAIS and CAH, and their generalizability and applicability need to be researched. 64,65 As we have to deal with controversies and knowledge gaps, matters of handling risk and uncertainty 66 and ways of dealing with specific dilemmas 41,67 play a crucial role.…”
Section: Decision-makingmentioning
confidence: 99%